Dying Alone Due to COVID-19: Do the Needs of the Many Outweigh the Rights of the Few—or the One? - Capozzo, Alejandra Victoria (2020)
The COVID-19 pandemic, caused by infection with the severe acute respiratory syndromecoronavirus 2 (SARS-CoV-2), has been striking the world since it was first identified in December2019 in China. The World Health Organization (WHO) declared the outbreak a ?public healthemergency of international concern? on January 30th, 2020, and recognized its pandemicstatus on March 11th. The pandemic has caused universal psychosocial impact (1) and globaleconomic disruption. Discourse and measures have been discussed focused on lockdown strategies,healthcare policies (2), application of emerging treatments, accelerated clinical trials, among others.Management guidelines are continuously updated based on emerging findings (3). However, as thedisease spreads through a community, suffering deepens due to strict procedures that, arguably,may be questioned from an ethical standpoint. The pandemic has sufficiently disrupted and impaired people’s livelihood worldwide, and every eﬀort to prevent any additional suﬀering must be made